Future competencies for three demanding careers of industry 4.0: Robotics engineers, data scientists, and food designers. Issue 2 (12th June 2021) - Rawboon, Khwanruethai; Yamazaki, Atsuko K.; Klomklieng, Wannaphop; Thanomsub, Wisa
Abstract: Introduction: The Asian region is now a pivotal driver of global economic growth. Urgent discussions are thus mandated on the forthcoming demands for qualifications generating broad‐based knowledge and skillsets related to emergent challenges posed by the new industrial revolution. A survey of competencies that will be required is crucial for Asian universities and higher education institutions in other regions because a large percentage of university graduates are shortly likely to work in Asian countries. Objective: This paper identified the future competencies for three careers that are representative of the demand for highly skilled personnel needed in potential industries during Industry 4.0: robotics engineers, data scientists, and food designers. Methods: This study describes the insights attained through a literature review, followed by an intensive investigation of the required competencies via focus group discussions and individual interviews. A questionnaire survey was administered and in‐depth interviews were conducted to confirm the future competencies essential for the three stated careers. Finally, the robustness of the conducted analyses was verified. Results: The findings revealed the demand for a diverse mix of competencies in the current and prospective Industry 4.0 environment. Future employers are likely to highlight multidisciplinary skills that may be categorized into three crucial groups: social, personal, and methodological. Conclusion: Universities and higher education institutions across the world should inculcate the required competencies in students to foster necessary knowledge and skills to meet the demands of changing workplaces and promising opportunities over the next decade.